Farm to Factory: A Reinterprétation of the Soviet Industrial Revolution - Clarke, Simon (Labour / Le Travail, 2005)
The article reviews the book, "Farm to Factory: A Reinterprétation of the Soviet Industrial Revolution," by Robert C. Allen.